Otoritas Musyawarah dalam Pengambilan Keputusan di Pemerintahan: Analisis Pendapat Imam Mawardi dalam Kitab Al Ahkam Sulthaniyah - Safriadi Safriadi; Munawar Khalil; Chalidin Chalidin (Ma'had Aly Raudhatul Ma'arif, 2026)
Consultation (musyawarah) is a fundamental principle in the Islamic system of governance that emphasizes participation and collective responsibility in decision-making. This qualitative study examines the authority of consultation through the perspective of Imam al-Mawardi in his book Al-Ahkam as-Sulthaniyah, using a content analysis approach. Unlike previous studies, which tend to repeat normative explanations of shura, this research focuses on al-Mawardi’s argumentative position and its relevance to contemporary governance. The results of the analysis show that, according to al-Mawardi, consultation is not merely an exchange of opinions but a legally binding mechanism for reaching consensus in state decision-making regarding matters of public interest. Leaders who fail to engage in musyawarah will face severe consequences, such as violating Allah’s command, becoming oppressive rulers, and causing division among the people. In conclusion, al-Mawardi’s intellectual framework offers a highly relevant political framework for institutionalizing the principle of musyawarah to prevent autocracy and strengthen political oversight in modern governance systems.